2021
DOI: 10.3390/agronomy11071306
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Zinc Fertilization in Calcareous Soils Improves Wheat (Triticum aestivum L.) Productivity and Soil Zinc Status in the Rice–Wheat Cropping System

Abstract: Rice–wheat cropping system (RWCS) is considered as the furthermost vital system in the Indo-Gangetic Plains of South-Asia, including India, Pakistan, Bangladesh, and Nepal. Recently, the deficiency of micronutrients like zinc (Zn) has emerged as one of the prime limitations for the sustainability issues of this RWCS in Zn deficient calcareous soils, particularly in India, as a result of the calcareous typic ustifluvents taxonomic nature of the soils. Therefore, a new Zn fertilization approach for soils is very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Straw yields of Tef were also reported significantly increased due to the application of NPSB on Vertisols of Hatsebo, central Tigray ( Tewolde, Gebreyohannes & Abrha, 2020 ), and application of K in Vertisols of central highland Ethiopia ( Demïss et al, 2020 ). The current finding by Lakshmi et al (2021) revealed a significantly higher SY where wheat was treated with 10 kg Zn ha −1 in calcareous soil. Application of Sulfur on Vertisol and Cambisol soil types reported improving straw yield in central highland Ethiopia ( Assefa, Shewangizaw & Kassie, 2020 ).…”
Section: Resultssupporting
confidence: 43%
See 1 more Smart Citation
“…Straw yields of Tef were also reported significantly increased due to the application of NPSB on Vertisols of Hatsebo, central Tigray ( Tewolde, Gebreyohannes & Abrha, 2020 ), and application of K in Vertisols of central highland Ethiopia ( Demïss et al, 2020 ). The current finding by Lakshmi et al (2021) revealed a significantly higher SY where wheat was treated with 10 kg Zn ha −1 in calcareous soil. Application of Sulfur on Vertisol and Cambisol soil types reported improving straw yield in central highland Ethiopia ( Assefa, Shewangizaw & Kassie, 2020 ).…”
Section: Resultssupporting
confidence: 43%
“…Sulfur is also an essential component of amino acids (like cysteine and methionine) crucial to protein formation and improves cereal crops’ milling and baking quality ( Clarkson & Hanson, 1980 ). Zinc is also engaged in more than 300 enzymes for protein and carbohydrate metabolism with a significant constitute for human immunity enhancement ( Lakshmi et al, 2021 ). Studies conducted so far to analyze the effect of N fertilizer on grain quality traits have also revealed significant increases in total GPC of rice, wheat, maize, and barley under an increased rate of N application ( Carson & Edwards, 2009 ; Chandel et al, 2010 ; Nishizawa, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zn deficiency is particularly prevalent in the areas where the soils are saturated with lime ( Genc et al., 2006 ). The calcareous, high phosphorus, and high organic matter content of soils reduces the amount of Zn available to crops ( Brennan and Bolland, 2006 ; Lakshmi et al., 2021 ). Therefore, the grain produced is Zn deficient, which in turn causes Zn deficiency in animals and humans consuming it.…”
Section: Introductionmentioning
confidence: 99%
“…For example, China and India rank second and third in urea consumption, respectively. However, this high demand comes at a cost, due to the unregulated application of these types of fertilizers, nutrient loss can occur, as indicated by Singh et al (2021), where India had a negative balance of approximately 8 to 10 MT year −1 , and the situation is expected to worsen, reaching 15 MT year −1 [ 2 , 3 , 4 ]. Furthermore, traditional NPK-type fertilizers have significant polluting potential, resulting from volatilization losses which generate atmospheric pollution and leaching of oxidized nutrients, which in turn contaminate aquifers.…”
Section: Introductionmentioning
confidence: 99%